Sorption of roxarsone onto soils with different physicochemical properties. (September 2016) - Fu, Qing-Long; He, Jian-Zhou; Blaney, Lee; Zhou, Dong-Mei
Abstract: Elevated roxarsone (ROX) concentrations in soils, caused by land application of ROX-bearing poultry litter, mandate investigation of ROX sorption onto soils. Equilibrium and kinetic studies of ROX sorption onto five soils were carried out to explore the relationship between sorption parameters and soil properties, and to reveal the effects of coexisting humic acid (HA), P(V), As(V), and As(III) on ROX transport. Experimental results indicated that ROX sorption reached equilibrium within 24 h, with pseudo-second order rate constants of 5.74–5.26 × 10 2  g/(mg h); film and intra-particle diffusion were the rate-limiting processes. ROX sorption to soils involved partitioning and adsorption phenomena; however, their relative contributions varied for different soils. The maximum ROX sorption varied with soil type, ranging from 0.59 to 4.12 mg/g. Results from correlation analysis and multiple linear regressions revealed that the maximum sorption capacities, partition coefficients, and desorption percentages were correlated with soil properties, especially iron content, total organic carbon, and dissolved organic carbon. ROX sorption to soils was affected more by soil pH than the initial pH of ROX-containing solutions. Carboxylic and amide functional groups were determined to be responsible for ROX sorption to soils. ROX sorption capacities decreased in the presence of HA, P(V), As(V), and As(III), indicating that ROX mobility in soils was facilitated by dissolved organic matter (DOM) and competing anions. Graphical abstract: Highlights: ROX sorption to soils was rate-limited by both film and intra-particle diffusion. Adsorption and partitioning were involved in the sorption of ROX to soils. ROX sorption parameters were influenced by soil FeDCB, TOC, and DOC. Acidic carboxylic and alkaline amide groups are responsible for ROX sorption. ROX mobility in soils is profoundly facilitated by soil DOM, P(V), As(III), As(V).